Weaning Method Evaluation for Beef Cattle - Jaymelynn K. Farney (Kansas Agricultural Experiment Station Research Reports, 2023)
Weaning is a stressful event for calves. Various management practices have been suggested to reduce weaning stress. The purpose of this study was to evaluate three different weaning management practices on calf gains at weaning. Eighty-eight bull and heifer calves were assigned to one of three weaning treatments at two research locations. The weaning management options were abrupt weaning, fence-line weaning, and use of a nose-flap weaning device. Calves were weighed at the start of the measurement period and then two weeks later after weaning was completed. Calves that were weaned using the nose-flap method had significantly lower gains than calves that were abruptly weaned or fence-line weaned. Bulls also gained more during this weaning period than heifers did. Generally, fence-line weaned calves have a greater gain than abruptly weaned calves, but in this study where the calves were abruptly weaned and only moved a few miles from the dams, we did not see a difference in gains during the weaning event between abrupt weaning and fence-line practices. The nose-flap device seemed to lead to a lower gain for calves during this period and more research on the device is needed before determining the best weaning management practice.
Keywords: fence-line weaning; abrupt weaning; two-step weaning